EVALUASI PROGRAM KELAS TAHFIDZ AL-QUR’AN BERBASIS CIPP (CONTEXT, INPUT, PROCESS, AND PRODUCT) DI SMPIT WAHDATUL UMMAH KOTA METRO - Zullaila Lutfi; Heri Cahyono; Iswati; Akbar Waliyuddin Pakpahan (PROFETIK: Jurnal Mahasiswa Pendidikan Agama Islam, 2026)
Almost all school institutions hold excellent programs, one of which is the tahfidz Al-Qur'an program, but a comprehensive evaluation has never been carried out, therefore the purpose of this study is to evaluate the tahfidz class program at SMPIT Wahdatul Ummah Metro city, using the CIPP (Context, Input, Process, and Product). This research is type of qualitative research. Data collection technique the data collection technique of this research is using interview, observation, and documentation. While the data analysis techniques used in this study are data reduction, data presentation, and data conclusion drawing. The results showed that the evaluation of the Qur'an tahfidz class program at SMPIT Wahdatul Ummah, showed that the context of the tahfidz class program was included in the school curriculum. In addition, the purpose of the tahfidz class program is to provide capital for students to have memorized the Qur'an and to improve the quality of reading (tahsin tajwid) of students. The input of the Qur'an tahfidz class program is the existence of other activities that support the tahfidz program so that it can take place well, namely joint muroja'ah activities held before the teaching and learning process begins, recitation together in the mosque, and Arabic language class activities. Process of the tahfidz class program is the implementation of the tahfidz program in class, running according to the schedule determined by the school, which is 8 hours in one week, and 2 hours / once a meeting. and the obstacle is the lack of learning time for tahfidz hours in class, as well as the lack of tahfidz tutors in class. The product of the Al-Qur'an tahfidz class program is the competency standards of students who graduate from the Al-Qur'an tahfidz program, namely not all students can achieve the targets set by the school. The conclusion is that the tahfidz class program at SMPIT Wahdatul Ummah is good to be continued and developed again, with a note of improvement in the process or implementation of the tahfidz class program.